2011
DOI: 10.5505/tjtes.2011.88557
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic Performed Focused Assesment with Sonography in Trauma (FAST) in the Emergency Department

Abstract: AMAÇTravmayı takiben acil servise başvuran hastalarda paramediklerce uygulanan travmaya odaklanmış ultrasonografi değerlendirmesinin (PFAST) serbest sıvı saptamadaki doğ-ruluğu araştırıldı. GEREÇ VE YÖNTEMDört saatlik teorik ve dört saatlik uygulamalı eğitim sonrası, dört paramedik travma hastalarını ileriye dönük inceledi. Altın standardımız ultrasonografi ve karın bilgisayarlı tomografisinin (KBT) resmi radyolog raporlarıydı. PFAST'in duyarlılık, seçicilik, pozitif ve negatif olabilirlik oranları ve tanısal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
(19 reference statements)
2
10
0
4
Order By: Relevance
“…This correlation was consistent with published findings by Unlüer et al [ 12 ] who reported a significant relationship between the qualification level of paramedics and their direct knowledge on ultrasound[ 12 ]. Additionally, this question was directed to Saudi Red Crescent managers and 80% of them reported that they had extensive background knowledge on ultrasound (Figure 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…This correlation was consistent with published findings by Unlüer et al [ 12 ] who reported a significant relationship between the qualification level of paramedics and their direct knowledge on ultrasound[ 12 ]. Additionally, this question was directed to Saudi Red Crescent managers and 80% of them reported that they had extensive background knowledge on ultrasound (Figure 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…The lowest ranges related to a study in mass casualty incidents [ 19 ]. Results for a complete FAST examination was only reported by one author with a sensitivity of 84.6% and specificity of 97.3% [ 18 ]. One study specifically reported a sensitivity and specificity of 100% for pericardial effusion as well as a sensitivity of 60% and specificity of 93% for abdominal trauma cases [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Substantial agreement (kappa = 0.67) between helicopter operator and expert reviewer who looked at images later. Reviewer rated 54% of the images taken as ‘good’ quality.Ulneur et al 2011 [18]Didactic & practicalApplication & interpretation4 h didactic training + 4 h hands-on trainingTraining was provided by a radiologist to conduct a FAST assessment. Results were recorded as positive/negative for free fluid in each case.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unluer et al conducted a study using four senior paramedics, involving a four-hour didactic and four-hour practical training program for FAST to detect free fluid in the peritoneum of 127 patients admitted to the emergency department following trauma [25,29]. The exam was performed in less than four minutes, with a Sn of 84.62% and Sp of 97.37%, compared to the gold standard of ultrasound and computerized abdominal tomography (CAT) scan interpretation by radiologists [25,29].…”
Section: Focused Assessment Sonography In Trauma (Fast)mentioning
confidence: 99%